FIRST JURASSIC EVIDENCE OF A POSSIBLE SPINOSAURID PEDAL UNGUAL, FROM THE JAISALMER BASIN, INDIA (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2023)
We describe an isolated, almost complete pedal ungual phalanx from the Middle Jurassic marine carbonate rocks of the Jaisalmer Basin, Rajasthan, north-western India. The ungual bone is triangular shaped, pointed, elongated, asymmetrical, dorsoventrally compressed, ventrally flat, bearing a shallow semi-circular excavation, and almost straight in lateral view. The morphological features, as well as its proportions closely resemble the pedal ungual phalanges of spinosaurid theropods, presently known dominantly from the Cretaceous. The affinity to spinosaurids is supported by bivariate and multivariate analyses. The ungual phalanx is tentatively identified as a basally branching Jurassic spinosaurid under Megalosauroidea. Considering the stratigraphical and geographical provenances, this contribution may represent the oldest record of a spinosaurid.
Keywords: Pedal ungual phalanx; Spinosauridae; Jaisalmer Basin; Middle Jurassic; Bathonian; Eastern Gondwana.